2021
DOI: 10.1097/hcr.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Women Have Lower Mortality Than Men After Attending a Long-Term Medically Supervised Exercise Program

Abstract: Medically supervised exercise programs (MSEPs) are equally recommended for men and women with cardiovascular disease (CVD). Aware of the lower CVD mortality in women, we hypothesized that among patients attending a MSEP, women would also have better survival. Methods: Data from men and women, who were enrolled in a MSEP between 1994 and 2018, were retrospectively analyzed. Sessions included aerobic, resistance, flexibility and balance exercises, and cardiopulmonary exercise test was performed. Date and underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Moreover, certain subpopulations, often those who need it most, are even less likely to access CR [8]. For instance, meta-analyses reveal women are signi cantly less likely to be referred and enroll [9,10], despite arguably greater need for many clinical (e.g., more comorbidity, lower functional capacity) and psychosocial (e.g., depression, lower socioeconomic status) reasons [11,12], and the demonstrated bene t in women [13,14]. There has been one study since which showed greater CR use in women [15]; This study was undertaken in Sweden, which is the 5th most gender equal country of the world, and the authors postulate in the discussion that this may explain the nding [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, certain subpopulations, often those who need it most, are even less likely to access CR [8]. For instance, meta-analyses reveal women are signi cantly less likely to be referred and enroll [9,10], despite arguably greater need for many clinical (e.g., more comorbidity, lower functional capacity) and psychosocial (e.g., depression, lower socioeconomic status) reasons [11,12], and the demonstrated bene t in women [13,14]. There has been one study since which showed greater CR use in women [15]; This study was undertaken in Sweden, which is the 5th most gender equal country of the world, and the authors postulate in the discussion that this may explain the nding [16].…”
Section: Introductionmentioning
confidence: 99%
“…2 Likewise, poor CRF is the fourth-leading risk factor for CVD and can predict mortality even better than hypertension (HTN), hyperlipidaemia or type 2 diabetes mellitus (T2DM). 3 The literature provides sufficient evidence regarding the association of modifiable lifestyle-related risk factors, including physical inactivity, sedentary lifestyle and obesity with CVD. 2 Physical activity is an effective and feasible intervention strategy to improve physical fitness and facilitate better neurocognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, women are less likely to participate in CR (Samayoa et al, 2014), which is particularly concerning given their greater need (Kawamoto et al, 2016; Mauvais‐Jarvis et al, 2020; McSweeney et al, 2016), that is, compared with men, they have greater social and economic disadvantage, they are diagnosed at more advanced stages of disease, they are treated less aggressively, they have more adverse effects from treatment, and they often have poorer outcomes (Vogel et al, 2021). Accordingly they may benefit to a greater degree than men (de Souza e Silva et al, 2021; Ekblom et al, 2021). Women's CR barriers have been extensively studied, and include lack of transportation/distance, depression/anxiety, lack of support/encouragement, comorbidities, and associated concern over pain or fatigue during exercise, as well as time conflicts due to their multiple role obligations (Grace et al, 2009; Supervia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly they may benefit to a greater degree than men (de Souza e Silva et al, 2021;Ekblom et al, 2021). Women's CR barriers have been extensively studied, and include lack of transportation/distance, depression/anxiety, lack of support/encouragement, comorbidities, and associated concern over pain or fatigue during exercise, as well as time conflicts due to their multiple role obligations (Grace et al, 2009;Supervia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%